PENGARUH FAKTOR KOMPENSASI, PIMPINAN, TEMAN SEKERJA, KEBIJAKAN ORGANISASI, DAN PEKERJAAN TERHADAP MOTIVASI KERJA PEGAWAI DINAS PEKERJAAN UMUM KABUPATEN BOJONEGORO - Edi Dwi Purwanto; Woro Utari; Wasis Budiarto (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2018)
This study aims to identify and describe the relationship between compensation factors, leadership, coworkers, organizational policies (agencies), the work itself to the work motivation of employees of Bojonegoro District Public Works Department. To know and analyze the influence of compensation factor, leadership, coworkers, organization policy (agency), work itself partially to work motivation of employee of Bojonegoro District Public Works Department. The population in this study is all employees of the Office of Bojonegoro District Public Works Department as many as 109 employees. Technique used in this research is purposive sampling that take sample research based on certain criterion. Data analysis technique used in this research is simple linear regression. The result of data analysis shows the compensation and job factors respectively partially have significant effect on employee work motivation of Bojonegoro District Public Works Department, and factors of leadership, coworkers and policy organization (institution) partially have no significant effect on employee work motivation. Compensation factors, leadership, coworkers, organizational policies (agencies), and the work itself simultaneously have a significant effect on employee work motivation of Bojonegoro District Public Works Department. Keywords: compensation, leadership, coworkers, policy, employment, work motivation